A Time For Renewal - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2017)
The Telecommunications Association has commenced the second phase of the renewal process that started in 2013. As part of the first phase of this renewal process a key decision was to relaunch the Telecommunications Journal of Australia as the Australian Journal of Telecommunications and the Digital Economy. In addition to the Journal, the Telecommunications Association holds the Henry Sutton and Charles Todd Orations each year in Melb0urne and Sydney respectively. As the second phase progresses, the Telecommunications Association will launch a new brand, update the Association’s website and host the first of what should become an annual two-day telecommunications forum. The first event is to be held in Melbourne in November. For the Journal, key milestones have now been achieved, including being added to the SCOPUS list of indexed Journals and the Australian Research Council’s Excellence in Research for Australia, which is the national research evaluation framework.